Head injury alert: A new level of trauma activation?. (July 2020) - Ricaurte, Daniel; Slack, Daniel; Gilson, Aaron; Nowicki, Michael; Nelson, Monika; Feinn, Richard; Zdankiewicz, Peter
Introduction: Trauma activation requires mobilization of significant resources to be available at short notice. In 2014, the American College of Surgeons Committee on Trauma issued its latest recommendations for care of the injured patient. Amongst trauma activation criteria, elderly patients that fell from any height on anticoagulation were included. We hypothesized that a reduced trauma team could preserve patient safety while reducing time and cost spent. Method: A 'Head Injury Alert' was created to denote anti-coagulated patients with a GCS > 14 who fell from a height of <20 feet. An ED attending, surgical resident and one nurse evaluate the patient with the goal of obtaining a head CT within 30 min of presentation. Data were prospectively acquired from June 2017 to August 2018, which included age, anticoagulation, injury severity score (ISS), time-to-CT, outcomes, missed injuries, disposition and activations requiring escalation of care. Results: Two hundred and seventy-seven head injury activations occurred; 55% of patients were female, while 45% were male. Average age was 78 years old. The most common anticoagulant was Warfarin (31%). 50% of patients were discharged, 47% were admitted, 2% died before disposition and 1% were transferred to a tertiary care center; 7% required admission to the ICU. The average time-to-CT was 25 min and ISS ranged from 0 to 26. Twenty-two patients (7%) presented with positive head CT. Of the five deaths, three patients had intracranial hemorrhage, one pneumonia present on admission and one cardiac arrest. Conclusion: This level III evidence, prospective study suggests head injury alert can be safely applied as a new level of trauma activation at community hospitals. It helps identify a specific patient population and injury mechanism that can be safely triaged using limited resources. With this, community hospitals can maximize their resources and minimize cost, while maintaining patient safety.